THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, WORK COMMUNICATION AND TEAMWORK ON EMPLOYEE PERFORMANCE AT THE REGIONAL STATE-OWNED BANK SOUTH JAKARTA BRANCH WITH WORK MOTIVATION AS MEDIATION - Saharso Saharso; Wieke Widya Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to examine and assess the impact of transformational leadership style, work communication, and teamwork on the performance of employees at Regional State-Owned Bank South Jakarta Branch through work motivation as mediation. This quantitative research study uses questionnaire collection techniques and Smart-PLS SEM with 100 employees as sample data. The findings show that transformational leadership style and work communication significantly positively influence work motivation, while teamwork does not significantly impact work motivation. In addition, transformational leadership style, work communication, and work motivation significantly positively influence employee performance but not teamwork. Another result is that work motivation cannot mediate work communication and teamwork on employee performance, but it can mediate the relationship between transformational leadership style and employee performance.